Street-art as a tool branding urban space (on the example of Ekaterinburg) - Olesya A. Blinova (Управление культурой)
The modern social context is such that it requires cities to define their own identity and uniqueness, which will further contribute to the growth of competitiveness, tourist and economic attractiveness. The basis for the formation of a city's identity is its brand and the process of its formation - branding. It is the presence of a city's own unique brand book that allows it to outline its advantages relative to neighboring territories, to identify the fundamental meanings of urban space through which residents can gain an urban identity that determines their inclusion in the life of the city and distinguishes their value system from the value system of residents of other cities in the country. Thanks to modern empirical and analytical methods of scientific research, the work analyzes the process of branding of urban space and its main tools: strategic, advertising, PR and symbolic. The author proposes the practice of street-art as a relevant, most modern and effective tool for city branding, aimed at creating a visual code of the city that conveys its creativity and uniqueness. The platform for analyzing street art as a tool for branding urban space was the city of Ekaterinburg, which is characterized by street artists as the most prepared and open for street art. As a result of the study, the main forms of the presence of street art in the space of Ekaterinburg were identified and described, the embodiment of which realizes the right to the city and creates some unique atmosphere of the city's space, denoting its originality and uniqueness, distinguishing it from other Russian cities. It is also concluded that residents of Ekaterinburg consider street art to be one of the main elements of their brand, expressing value, socio-political and cultural foundations, allowing them to realize their “right to the city” and having a positive impact on the formation of their identity as Ekaterinburg residents and the formation of a local patriotism.